ANALYZING THE INFLUENCE OF BUILDING MASS ORIENTATION ON ENERGY EFFICIENCY AND SUSTAINABLE BUILDING PERFORMANCE - Alderina Rosalia; Onie Dian Sanitha; Fredyantoni F. Adji; Elis Sri Rahayu; Velly Vurna; Jeremy Junior Kurniawan; Dennis Sandy Laurentius Situmorang (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
Building mass orientation is one of the fundamental parameters of passive design strategies that significantly influences energy efficiency, daylight performance, and thermal comfort in sustainable architecture. This study aims to analyze the influence of building mass orientation on the achievement of sustainable building performance in tropical humid climates. The research adopts a quantitative– descriptive approach using climate-based simulations, employing parameters such as Useful Daylight Illuminance (UDI), Annual Sunlight Exposure (ASE), and Cooling Load Analysis. The findings indicate that the existing building orientation facing northwest–southeast generates an excessive level of natural lighting, with UDI-Above reaching 86.3%, implying an overlighting condition. Meanwhile, the ASE average of 7.15 hours per year suggests that the interior spaces are almost entirely protected from direct sunlight exposure. This combination leads to uneven daylight distribution and high indoor temperatures, averaging 31–32°C with relative humidity between 70–75%. An alternative simulation, with a rotation of ±15° toward the north–south axis and the addition of horizontal shading devices, shows a reduction in cooling energy consumption by 18–22% and an improvement in thermal comfort of approximately 1.5°C lower than the existing condition. The results confirm that building mass orientation has a substantial impact on both energy performance and occupant comfort. Passive design strategies such as horizontal and vertical shading devices, light shelves, and vegetative buffers can effectively optimize daylight use while reducing thermal loads. This study contributes empirical evidence supporting the application of passive tropical design principles and sustainable architecture in educational and institutional buildings.